Antimony-free flame-retardant cable material as well as preparation method and application thereof
By designing a multi-dimensional crosslinking network structure in cable materials, using components such as polyolefin and butadiene-based polymers, the problem of poor stability of traditional cable materials in high temperature and high humidity environments is solved, and high-performance flame-retardant cable materials without halogen and antimony are achieved.
Patent Information
- Application Number
- CN202411971995.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-25
AI Technical Summary
It is difficult for existing cable materials to maintain stable operation in high temperature and high humidity environments, and traditional flame retardants have pollution problems with halogen and antimony systems, which affects environmental protection.
By designing and combining polyolefins, butadiene-based polymers, alkenyl ring triphosphazene, alkenyl oligosilsesquioxane and antimony-free flame retardant, a multi-dimensional crosslinking network structure is formed and covalently embedded in the crosslinking network to achieve excellent flame retardant, mechanical, high temperature and humidity resistance.
It has achieved halogen-free and antimony-free cable materials, with excellent flame retardancy, mechanical properties, high-temperature aging resistance and humidity and heat resistance, and can continue to operate stably in high-temperature and high-humidity environments, meeting environmental protection requirements.
Smart Images

Figure BDA0005219675360000031 
Figure BDA0005219675360000061 
Figure BDA0005219675360000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cable materials, and in particular relates to an antimony-free flame-retardant cable material and a preparation method and application thereof. Background Art
[0002] Electricity is an indispensable resource for social development and people's lives. The performance of cable materials directly affects the stable operation of the power system. Polyvinyl chloride (PVC) is one of the most commonly used raw materials for domestic cable materials. It has the characteristics of low cost, light weight, sufficient raw materials, good mechanical properties and electrical insulation. However, PVC cable materials are prone to fire when the current is overloaded, and PVC will release a lot of thick smoke and toxic fumes during combustion, which is extremely harmful to personnel health and surrounding facilities. Therefore, the development of environmentally friendly cable materials is very important.
[0003] In recent years, polyolefin materials represented by polyethylene (PE) have been widely used in cable materials, gradually replacing PVC and becoming a typical product of environmentally friendly cable materials. Since polyolefin itself is flammable, it must be flame-retardant treated when used in cables.
[0004] CN114456461A discloses a flame retardant polyethylene cable material, the components of which are as follows: 5-15 parts of ethylene vinyl acetate, 15-30 parts of high-fluidity high-density polyethylene, 20-50 parts of high-elongation low-density polyethylene, 20-40 parts of inorganic flame retardant, 1-3 parts of silicone, 1-3 parts of stearic acid, and 2-5 parts of environmentally friendly bromine antimony flame retardant; wherein the inorganic flame retardant is at least one of aluminum hydroxide, magnesium hydroxide and coated red phosphorus, and the environmentally friendly bromine antimony flame retardant is a mixture of decabromodiphenylethane or brominated polystyrene and antimony trioxide. The cable material can meet the combustion grade of bundled A grade while having better performance than conventional cable sheath materials.
[0005] CN106117754A discloses a flame retardant antistatic polyethylene material, which is prepared from the following components by mass percentage: polyethylene resin 70-80%, coupling agent 1-7%, flame retardant 2-10%, antimony trioxide 1-5%, antistatic agent 2-12%, basalt fiber 1-9%; wherein the flame retardant is one of decabromodiphenyl ether, hexabromocyclododecane, octabromoether, and tetrabromobisphenol A. The flame retardant antistatic polyethylene material is used to prepare cable pipes, and has the characteristics of good flame retardancy and good antistatic effect.
[0006] CN118359864A discloses a cable material for energy storage cable, including a specific gravity of ≥1.4g / cm 3The raw materials of component A include: a first base resin, a first flame retardant, a silane coupling agent and an initiator, and the raw materials of component B include: a second base resin, a second flame retardant and a catalyst; the first base resin and the second base resin both include ethylene-vinyl acetate copolymer, linear low-density polyethylene, POE resin and maleic anhydride grafted POE resin; the first flame retardant and the second flame retardant both include the following components with specific particle size and weight specific surface area: decabromodiphenylethane, antimony trioxide, magnesium hydroxide and aluminum hydroxide. The filling amount of the flame retardant in the cable material is high, and on the basis of silane cross-linking, it can overcome the problems of excessive silane grafting or pre-cross-linking caused by high filling of flame retardant fillers.
[0007] At present, the flame retardants widely used in cable materials include metal hydroxides, halogen flame retardants, antimony flame retardants, etc. Among them, halogen flame retardants release hydrogen halides (such as HBr, HCl, etc.) during combustion or degradation. Such acidic gases pose a threat to human health and the environment. Therefore, environmentally friendly cable products usually require halogen-free. Antimony flame retardants have the advantages of being cheap and having good flame retardant effects. However, antimony compounds themselves have certain toxicity. Major environmental protection organizations have begun to limit the antimony content in controlled products. Therefore, antimony-free cable materials have become an important research topic at present. In the face of the requirements of halogen-free and antimony-free, the industry uses metal hydroxides such as magnesium hydroxide and aluminum hydroxide for flame retardancy. Such flame retardants can only exert good flame retardancy when added in large amounts, but the addition of a large amount of flame retardants will lead to serious deterioration of the mechanical properties, heat resistance and moisture and heat resistance of cable materials.
[0008] Therefore, developing halogen-free and antimony-free cable materials with excellent mechanical properties, high temperature resistance and moisture and heat resistance is an urgent problem to be solved in this field. Summary of the invention
[0009] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an antimony-free flame-retardant cable material and a preparation method and application thereof. Through the design and mutual compounding of each component, a stable cross-linking system is formed, and the flame retardant component is covalently embedded in the cross-linked network structure, so that the antimony-free flame retardant cable material can achieve excellent flame retardant effect while having excellent mechanical properties, high temperature aging resistance and moisture and heat resistance, and can meet the continuous and stable operation requirements of cable materials in harsh environments such as high temperature and high humidity.
[0010] To achieve this object, the present invention adopts the following technical solutions:
[0011] In a first aspect, the present invention provides an antimony-free flame-retardant cable material, wherein the raw materials for preparing the antimony-free flame-retardant cable material include the following components in parts by mass:
[0012]
[0013] The present invention uses polyolefin as the matrix material, which is compounded with a butadiene-based polymer, an initiator and a co-crosslinking agent, and can form a specific crosslinking structure through a free radical mechanism crosslinking reaction, thereby increasing the degree of crosslinking and improving the mechanical properties, heat resistance and moisture-heat resistance of the cable material.
[0014] In the present invention, the alkenyl cyclotriphosphazene is a reactive nitrogen-phosphorus flame retardant, and the alkenyl oligomeric silsesquioxane contains reactive alkenyl groups and Si-O-Si skeletons. On the one hand, the nitrogen-phosphorus flame-retardant alkenyl cyclotriphosphazene, the silicon-based flame-retardant alkenyl oligomeric silsesquioxane and the antimony-free flame retardant are compounded to synergistically exert excellent flame retardant effects; on the other hand, the alkenyl functional groups in the alkenyl cyclotriphosphazene and the alkenyl oligomeric silsesquioxane react with the organic system (including polyolefins, initiators, and co-crosslinking agents) in a free radical mechanism to embed the cyclotriphosphazene structure and the Si-O-Si skeleton into the crosslinking network in the form of covalent bonds, so that the cable material has an intrinsic flame retardant effect, and at the same time, a multidimensional crosslinking system comprising carbon-carbon bonds, nitrogen-phosphorus rings and Si-O-Si structures is constructed, so as to further improve the mechanical properties, high temperature stability and moisture and heat resistance of the cable material.
[0015] In summary, the present invention forms a specific multi-dimensional cross-linked network structure through the design and mutual compounding of each component, so that the antimony-free flame-retardant cable material has excellent mechanical properties, high temperature aging resistance and moisture and heat resistance while achieving excellent flame retardant effect, and can meet the continuous and stable operation requirements of cable materials in harsh environments such as high temperature and high humidity.
[0016] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] In the preparation raw materials of the present invention, the mass parts of the polyolefin are 60-100 parts, for example, it can be 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 78 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts, 92 parts, 95 parts or 98 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0018] The mass parts of the butadiene-based polymer are 5-25 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts or 24 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the said range.
[0019] The mass parts of the alkenyl cyclotriphosphazene are 10-50 parts, for example, 12 parts, 15 parts, 18 parts, 20 parts, 22 parts, 25 parts, 28 parts, 30 parts, 32 parts, 35 parts, 38 parts, 40 parts, 42 parts, 45 parts or 48 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0020] The mass fraction of the alkenyl oligomeric silsesquioxane is 2-10 parts, for example, it can be 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0021] The mass parts of the antimony-free flame retardant are 30-80 parts, for example, 35 parts, 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts or 75 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0022] The mass fraction of the initiator is 0.1-5 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific point values between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0023] The weight percentage of the auxiliary cross-linking agent is 0.1-5 parts, for example, it can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.2 parts, 3.5 parts, 3.8 parts, 4 parts, 4.2 parts, 4.5 parts or 4.8 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0024] Preferably, the polyolefin includes any one of polyethylene, polypropylene, ethylene-propylene rubber, and polyolefin elastomer, or a combination of at least two thereof, and more preferably a combination of polyethylene and polyolefin elastomer.
[0025] Preferably, the polyolefin comprises the following components in parts by mass:
[0026] Polyethylene 60-80 parts
[0027] Polyolefin elastomer 5-20 parts.
[0028] Preferably, the mass fraction of the polyethylene is 60-80 parts, for example, it can be 62 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts or 78 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0029] Preferably, the mass parts of the polyolefin elastomer are 5-20 parts, for example, 6 parts, 8 parts, 10 parts, 12 parts, 14 parts, 15 parts, 16 parts or 18 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0030] Preferably, the polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof.
[0031] Preferably, the polyolefin elastomer comprises ethylene-octene copolymer (POE).
[0032] Preferably, the melt index of the polyolefin elastomer at 190°C and 2.16kg is 1-20g / 10min, for example, it can be 2g / 10min, 3g / 10min, 4g / 10min, 5g / 10min, 6g / 10min, 7g / 10min, 8g / 10min, 9g / 10min, 10g / 10min, 12g / 10min, 14g / 10min, 15g / 10min, 16g / 10min or 18g / 10min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 1.2-8g / 10min is further preferred.
[0033] Preferably, the butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer, or a combination of at least two thereof.
[0034] Preferably, the butadiene-based polymer comprises a structural unit represented by formula I:
[0035]
[0036] Preferably, the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-95%, for example, it can be 25%, 30%, 35%, 40%, 45%, 50%, 52%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 88% or 90%, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 40-90% is further preferred.
[0037] In the present invention, the butadiene-based polymer contains the 1,2-vinyl structural unit shown in Formula I, and the vinyl in the side chain has a high reactivity, and can undergo a free radical crosslinking reaction with a co-crosslinking agent, alkenyl cyclotriphosphazene, alkenyl oligomeric silsesquioxane and polyolefin under the action of an initiator, forming a specific multidimensional crosslinked network structure in the cable material, so that the antimony-free flame-retardant cable material has excellent mechanical properties, high temperature resistance and moisture and heat resistance. If the butadiene-based polymer does not contain the 1,2-vinyl structural unit shown in Formula I or its content is too low, the crosslinking degree will be reduced, resulting in a decrease in the mechanical properties, high temperature resistance and moisture and heat resistance of the cable material.
[0038] Preferably, the number average molecular weight of the butadiene-based polymer is 1000-10000, for example, it may be 2000, 3000, 4000, 5000, 6000, 7000, 8000 or 9000, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0039] Preferably, the mass ratio of the polyolefin elastomer to the butadiene-based polymer is 1:(1-3), for example, it can be 1:1.1, 1:1.2, 1:1:1.3, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.6 or 1:2.8, etc.
[0040] Preferably, the alkenyl cyclotriphosphazene has a structure as shown in Formula II:
[0041]
[0042] In formula II, R1, R2, R3, R4, R5, and R6 are each independently selected from any one of a phenyl group and a C2-C10 alkenyl-substituted phenyl group, and at least one (e.g., 2, 3, 4, 5, 6) of R1, R2, R3, R4, R5, and R6 is a C2-C10 alkenyl-substituted phenyl group.
[0043] Wherein, the C2-C10 alkenyl group can be a straight chain or branched alkenyl group of C2, C3, C4, C5, C6, C7, C8, C9, C10, containing at least one C=C, illustratively including but not limited to: vinyl, propenyl, allyl, butenyl, pentenyl, hexenyl, heptenyl, octenyl, nonenyl, decenyl, butadienyl, pentadienyl, etc.
[0044] Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is ——* indicates the attachment site of the group.
[0045] R is selected from any one of C2-C10 (e.g., C3, C4, C5, C6, C7, C8, C9, etc.) alkenyl groups, preferably vinyl, propenyl or allyl.
[0046] Among the R1, R2, R3, R4, R5 and R6 The number is 1-6, for example 1, 2, 3, 4, 5 or 6; preferably 2-6.
[0047] Preferably, the alkenyl oligomeric silsesquioxane has a polyhedral structure, and is preferably an alkenyl-containing cage-shaped oligomeric silsesquioxane.
[0048] Preferably, the alkenyl oligomeric silsesquioxane includes any one of octavinyl cage oligomeric silsesquioxane, octamethacrylate cage oligomeric silsesquioxane, octaacrylate cage oligomeric silsesquioxane, octaacryloxy cage oligomeric silsesquioxane, octamethacryloxy cage oligomeric silsesquioxane, and methacryloxypropyl cage polysilsesquioxane, or a combination of at least two thereof.
[0049] Preferably, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclotriphosphazene is 1:(3-10), for example, it can be 1:3.5, 1:4, 1:1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9 or 1:9.5, etc.
[0050] As a preferred technical solution of the present invention, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclotriphosphazene is 1:(3-10), which together with the antimony-free flame retardant constitutes a flame retardant system, giving the antimony-free flame retardant cable material excellent flame retardant properties, and at the same time undergoes a free radical cross-linking reaction with the co-crosslinking agent, butadiene-based polymer and polyolefin, constructing a multidimensional cross-linking system containing carbon-carbon bonds, nitrogen-phosphorus rings and Si-O-Si structures in the cable material, so that the antimony-free flame retardant cable material has excellent mechanical properties, high temperature resistance and wet heat resistance stability. If the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclotriphosphazene exceeds the preferred range of the present invention, it will not only affect the flame retardant properties, resulting in a decrease in the oxygen index, but also affect the stability of the material under high temperature and wet heat.
[0051] Preferably, the antimony-free flame retardant includes any one of aluminum hydroxide, magnesium hydroxide, zinc borate, and zinc stannate, or a combination of at least two thereof, and a combination of aluminum hydroxide and zinc borate is further preferred.
[0052] Preferably, the mass ratio of the aluminum hydroxide to the zinc borate is (1.5-4):1, for example, it can be 1.6:1, 1.8:1, 2:1, 2.2:1, 2.5:1, 2.8:1, 3:1, 3.2:1, 3.5:1, 3.8:1, etc.
[0053] Preferably, the initiator comprises an organic peroxide, further preferably any one or a combination of at least two of diisopropylbenzene hydroperoxide, dibenzoyl peroxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide, tert-butyl perbenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di(4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, cyclohexanone peroxide, and tert-butyl peroxy-3,5,5-trimethylhexanoate.
[0054] Preferably, the auxiliary cross-linking agent is a compound containing at least 2 (≥2, such as 2, 3, 4, 5, 6, etc.) unsaturated groups (such as alkenyl groups).
[0055] Preferably, the auxiliary cross-linking agent includes any one of pentaerythritol triacrylate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, and propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.
[0056] Preferably, the preparation raw materials further include any one or a combination of at least two of a compatibilizer, a lubricant, a silane coupling agent, a stabilizer, an ultraviolet absorber, and an antioxidant.
[0057] Preferably, the preparation raw materials also include 1-10 parts of compatibilizer in parts by mass, and the mass parts of the compatibilizer can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts or 9 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0058] Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof.
[0059] Preferably, the preparation raw material also includes 0.1-5 parts of lubricant by mass, and the mass parts of the lubricant can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0060] Preferably, the lubricant includes any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof.
[0061] Preferably, the preparation raw materials also include 0.1-5 parts of stabilizer by mass, and the mass parts of the stabilizer can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0062] Preferably, the stabilizer includes any one of calcium stearate, zinc stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) or a combination of at least two thereof.
[0063] Preferably, the preparation raw materials further include 0.1-5 parts of a silane coupling agent by mass, and the mass parts of the silane coupling agent can be 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2 parts, 2.2 parts, 2.5 parts, 2.8 parts, 3 parts, 3.5 parts, 4 parts or 4.5 parts, as well as specific points between the above points. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific points included in the range.
[0064] Preferably, the silane coupling agent includes any one of an alkenyl-containing silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof.
[0065] Further preferably, the silane coupling agent includes any one of vinyltriethoxysilane, vinyltrimethoxysilane, γ-(methacryloxy)propyltrimethoxysilane, methacryloxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-mercaptopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of at least two thereof.
[0066] In a second aspect, the present invention provides a method for preparing the antimony-free flame-retardant cable material as described in the first aspect, the preparation method comprising:
[0067] The prepared raw materials are mixed and extruded to obtain granules;
[0068] The particles are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the antimony-free flame-retardant cable material.
[0069] The preparation method of the antimony-free flame-retardant cable material provided by the present invention includes two cross-linking processes, the first cross-linking is heat-induced cross-linking, which mainly occurs during the mixing process, so that the obtained particles contain a certain cross-linking network. After the particles are processed into wires, they are irradiated and cross-linked by an electron accelerator, and the material system undergoes secondary cross-linking to obtain a specific multi-dimensional cross-linked network structure, so that the antimony-free flame-retardant cable material has excellent flame retardancy, mechanical properties, high temperature resistance, and moisture and heat resistance.
[0070] Preferably, the mixing is carried out in an internal mixer.
[0071] Preferably, the mixing temperature is 150-180°C, for example, it can be 155°C, 160°C, 162°C, 165°C, 168°C, 170°C, 172°C, 175°C or 178°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0072] Preferably, the mixing time is 5-30 min, for example, it can be 6 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0073] Preferably, the extrusion granulation is carried out in a screw extruder, such as a single-screw extruder or a twin-screw extruder.
[0074] Preferably, the operating temperature of the screw extruder is 100-150°C, for example, it can be 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C or 145°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range, and 110-130°C is further preferred.
[0075] Preferably, the screw extruder comprises a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone and a seventh zone connected in sequence, and the temperature of each zone is independently 105-130°C, for example, it can be 106°C, 108°C, 110°C, 112°C, 115°C, 118°C, 120°C, 122°C, 125°C or 128°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0076] Preferably, the temperature of the first zone in the screw extruder is 105-115°C (e.g., 106°C, 108°C, 110°C, 111°C, 112°C, 113°C, 114°C or 115°C, etc.), the temperature of the second zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), the temperature of the third zone is 115-120°C (e.g., 115°C, 116°C, 117°C, 118°C, 119°C or 120°C, etc.), and the temperature of the fourth zone is 120-125 ℃ (for example, 120℃, 121℃, 122℃, 123℃, 124℃ or 125℃, etc.), the temperature of the fifth zone is 120-125℃ (for example, 120℃, 121℃, 122℃, 123℃, 124℃ or 125℃, etc.), the temperature of the sixth zone is 120-130℃ (for example, 120℃, 122℃, 124℃, 126℃, 128℃ or 130℃, etc.), and the temperature of the seventh zone is 125-130℃ (for example, 125℃, 126℃, 127℃, 128℃, 129℃ or 130℃, etc.).
[0077] Preferably, the operating temperature of the wire extruder is 120-190°C, for example, it can be 125, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0078] Preferably, the wire extruder comprises a zone A, a zone B, a zone C and a zone D connected in sequence, so that the pellets can pass through zone A, zone B, zone C and zone D in sequence, wherein the operating temperature of zone A is 150-160°C (e.g., 152°C, 154°C, 155°C, 158°C, 159°C, etc.), the operating temperature of zone B is 160-180°C (e.g., 162°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C, etc.), the operating temperature of zone C is 160-180°C (e.g., 162°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C, etc.), and the operating temperature of zone D is 160-180°C (e.g., 162°C, 165°C, 168°C, 170°C, 172°C, 175°C, 178°C, etc.).
[0079] Preferably, the dose of the radiation cross-linking is 2-12 Mrad, for example, it can be 3 Mrad, 4 Mrad, 4.5 Mrad, 5 Mrad, 5.5 Mrad, 6 Mrad, 6.5 Mrad, 7 Mrad, 7.5 Mrad, 8 Mrad, 8.5 Mrad, 9 Mrad, 9.5 Mrad, 10 Mrad or 11 Mrad, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0080] In a third aspect, the present invention provides a use of the antimony-free flame-retardant cable material as described in the first aspect in building cables, wind power generation devices, solar power generation devices or electronic and electrical wires.
[0081] Compared with the prior art, the present invention has the following beneficial effects:
[0082] (1) In the antimony-free flame-retardant cable material provided by the present invention, the raw material components are designed and compounded with each other to form a synergistic effect, forming a cross-linking system jointly constructed by polyolefins, butadiene polymers, alkenyl cyclotriphosphazenes, alkenyl oligomeric silsesquioxanes, co-crosslinking agents, etc., and having a specific multi-dimensional cross-linked network structure in the cable material, so that the antimony-free flame-retardant cable material has excellent mechanical properties, high temperature aging resistance and moisture and heat resistance while achieving excellent flame retardant effect, and can meet the continuous and stable operation requirements of cable materials in harsh environments such as high temperature and high humidity.
[0083] (2) Through further design and optimization of the components, the present invention makes the antimony-free flame-retardant cable material have a tensile strength of ≥16.1 MPa, an elongation at break ≥400%, a change rate of elongation at break after aging at 180°C for 10 days of ≤7.1%, a change rate of elongation at break after double 85 test for 10 days of ≤8.3%, can pass single vertical combustion, has an oxygen index of ≥32%, has excellent comprehensive performance in flame retardancy, mechanical properties, high temperature resistance and moisture and heat resistance, and is halogen-free and antimony-free, meeting environmental protection requirements. DETAILED DESCRIPTION
[0084] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0085] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0086] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes cases where the event occurs and cases where it does not.
[0087] In the following specific implementation of the present invention, the specific information of the materials used is as follows:
[0088]
[0089]
[0090] The following will take multiple embodiments as examples to describe in detail the antimony-free flame-retardant cable material and the preparation method thereof of the present invention, but the antimony-free flame-retardant cable material and the preparation method thereof of the present invention are not limited to these embodiments.
[0091] Examples 1-8, Comparative Examples 1-7
[0092] An antimony-free flame-retardant cable material, the raw materials for its preparation are shown in Table 1 and Table 2, and the dosage unit of each component is "part".
[0093] The preparation method of the antimony-free flame-retardant cable material is as follows:
[0094] (1) adding each component into a mixer according to the formula amount, premixing for 5 minutes to obtain a mixture; adding the mixture into an internal mixer, mixing at 160° C. for 20 minutes, and extruding and granulating through a single screw extruder to obtain granules; the operating temperatures of zones 1 to 7 in the single screw extruder are 110° C., 115° C., 115° C., 125° C., 125° C., 120° C., and 120° C., respectively.
[0095] (2) adding the particles obtained in step (1) into a wire extruder and extruding to obtain wires, wherein the operating temperatures of the AD zone in the wire extruder are 150° C., 165° C., 170° C., and 170° C., respectively; irradiating the wires with an electron accelerator for cross-linking, and the irradiation dose is 5 Mrad to obtain the antimony-free flame-retardant cable material.
[0096] The following performance tests are conducted on antimony-free flame-retardant cable materials:
[0097] (1) Single vertical burning: Tested according to the method in GB / T 18380-2008.
[0098] (2) Oxygen index: tested according to the method in standard GB / T 2406.2-2009.
[0099] (3) Tensile strength and elongation at break: tested according to the method in standard GB / T 2951.11-2008.
[0100] (4) Heat resistance: After the cable material to be tested is aged at 180°C for 240 h, its elongation at break is tested and compared with the elongation at break measured in (3) to obtain the change rate; the change rate = the difference in elongation at break before and after aging / the original test value; the smaller the change rate, the better the heat resistance.
[0101] (5) Moisture and heat resistance: The cable material to be tested is placed in a moisture and heat aging test chamber at 85°C and 85% humidity. After 240 hours, the elongation at break is tested and compared with the elongation at break measured in (3) to obtain the change rate; the change rate = the difference in elongation at break before and after moisture and heat aging / original test value; the smaller the change rate, the better the moisture and heat resistance.
[0102] The test results are shown in Table 1 and Table 2.
[0103] Table 1
[0104]
[0105]
[0106] Table 2
[0107]
[0108]
[0109] According to the performance test data in Table 1, the present invention prepares the raw materials by designing and compounding each component to make it undergo free radical crosslinking reaction, form a specific multi-dimensional crosslinked network structure in the cable material, so that the antimony-free flame retardant cable material has excellent flame retardancy, mechanical properties, high temperature aging resistance and moisture and heat resistance. As some preferred technical schemes of the present invention, Examples 1-5 can pass single vertical combustion, oxygen index is 32-34%, tensile strength is 16.1-16.5MPa, elongation at break is 409-431%, elongation at break after aging at 180°C for 10 days is 6.4-7.1%, and elongation at break after double 85 moisture and heat test for 10 days is 7.9-8.3%, with outstanding performance in mechanical properties, heat aging stability and moisture and heat resistance.
[0110] Further, in combination with the effect data of Example 1 and Examples 6-8, it can be seen that the present invention realizes the regulation of the cross-linked structure by designing the content of 1,2-vinyl structural units in the butadiene-based polymer, designing and further optimizing the dosage of alkenyl oligomeric silsesquioxane and alkenyl cyclotriphosphazene, thereby synergistically improving the flame retardancy, mechanical properties, heat resistance and moisture and heat resistance of the cable material. The 1,2-vinyl structural unit content of the butadiene-based polymer in Example 6 is relatively low, resulting in a decrease in the cross-linking density, which affects the mechanical properties, heat resistance and moisture and heat resistance of the cable material. The dosage ratio of alkenyl oligomeric silsesquioxane to alkenyl cyclotriphosphazene in Examples 7-8 exceeds the preferred 1: (3-10) of the present invention, resulting in a decrease in the oxygen index of the material, and also having varying degrees of influence on the mechanical properties, heat resistance and moisture and heat resistance.
[0111] In the antimony-free flame-retardant cable material provided by the present invention, each component is designed and compounded to cooperate with each other, forming a cross-linking system jointly constructed by polyolefin, butadiene-based polymer, alkenyl cyclotriphosphazene, alkenyl oligomeric silsesquioxane, co-crosslinking agent, etc., and having a specific multi-dimensional cross-linked network structure in the cable material, so that the antimony-free flame-retardant cable material has excellent flame retardancy, mechanical properties, heat resistance and wet heat resistance. Comparison of Table 1 and Table 2 shows that Comparative Example 1 does not contain butadiene-based polymer, and Comparative Example 2 contains hydrogenated SEBS. Since the system does not contain reactive side chain vinyl, the cross-linking degree of the cable material is insufficient, resulting in a significant reduction in its tensile strength, elongation, heat aging resistance and wet heat aging resistance. Comparative Example 3 uses alkenyl-free hexaphenoxy cyclotriphosphazene, and Comparative Example 4 uses alkenyl-free oligomeric silsesquioxane, so it is only an additive flame retardant, and does not form an intrinsic flame retardant effect in the cable material, which not only leads to a decrease in the oxygen index, but also changes the cross-linking structure of the system, and the mechanical properties, heat resistance and wet heat resistance also decrease to varying degrees. Comparative Example 5 does not contain alkenyl oligomeric silsesquioxane, and Comparative Example 6 does not contain alkenyl cyclotriphosphazene. The cable material does not form a synergistic flame retardant system of nitrogen, phosphorus and silicon, and does not have a specific cross-linking network, resulting in deterioration of flame retardancy, mechanical properties, heat resistance and wet heat resistance. Comparative Example 7 does not contain an initiator, and it is difficult for each component to undergo a heat-induced cross-linking reaction during the mixing stage. The cross-linking structure obtained by relying solely on radiation cross-linking is not dense enough, resulting in a significant decrease in the mechanical properties, heat aging resistance and wet heat aging resistance of the cable material.
[0112] The applicant declares that the present invention illustrates the antimony-free flame-retardant cable material and its preparation method and application through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. An antimony-free flame-retardant cable material, characterized in that: The raw materials for preparing the antimony-free flame-retardant cable material include the following components in parts by mass:
2. The antimony-free flame-retardant cable material according to claim 1, characterized in that: The polyolefin comprises any one of polyethylene, polypropylene, ethylene-propylene rubber, and polyolefin elastomer, or a combination of at least two thereof, preferably a combination of polyethylene and polyolefin elastomer; Preferably, the polyolefin comprises the following components in parts by mass: Polyethylene 60-80 parts Polyolefin elastomer 5-20 parts; Preferably, the polyethylene includes any one of linear low-density polyethylene, high-density polyethylene, and metallocene polyethylene, or a combination of at least two thereof; Preferably, the polyolefin elastomer has a melt index of 1-20 g / 10 min at 190° C. and 2.16 kg.
3. The antimony-free flame-retardant cable material according to claim 1 or 2, characterized in that: The butadiene-based polymer includes any one of polybutadiene and butadiene-styrene copolymer or a combination of at least two thereof; Preferably, the butadiene-based polymer comprises a structural unit represented by formula I, and the molar percentage of the structural unit represented by formula I in the butadiene-based polymer is 20-95%; 4. The antimony-free flame-retardant cable material according to any one of claims 1 to 3, characterized in that: The alkenyl cyclotriphosphazene has a structure as shown in Formula II: Wherein, R1, R2, R3, R4, R5, and R6 are each independently selected from any one of phenyl and C2-C10 alkenyl-substituted phenyl, and at least one of R1, R2, R3, R4, R5, and R6 is C2-C10 alkenyl-substituted phenyl; Preferably, R1, R2, R3, R4, R5, and R6 are each independently selected from phenyl, Any one of, and at least one of R1, R2, R3, R4, R5 and R6 is R is selected from vinyl, propenyl or allyl.
5. The antimony-free flame-retardant cable material according to any one of claims 1 to 4, characterized in that: The alkenyl oligomeric silsesquioxane includes any one of octavinyl cage-type oligomeric silsesquioxane, octamethacrylate cage-type oligomeric silsesquioxane, octaacrylate cage-type oligomeric silsesquioxane, octaacryloxy cage-type oligomeric silsesquioxane, octamethacryloxy cage-type oligomeric silsesquioxane, and methacryloxypropyl cage-type polysilsesquioxane, or a combination of at least two thereof; Preferably, the mass ratio of the alkenyl oligomeric silsesquioxane to the alkenyl cyclotriphosphazene is 1:(3-10).
6. The antimony-free flame-retardant cable material according to any one of claims 1 to 5, characterized in that: The antimony-free flame retardant includes any one of aluminum hydroxide, magnesium hydroxide, zinc borate, and zinc stannate, or a combination of at least two thereof; Preferably, the initiator comprises an organic peroxide, preferably any one or a combination of at least two of diisopropylbenzene hydroperoxide, dibenzoyl peroxide, isopropylbenzene hydroperoxide, di-tert-butyl peroxide, tert-butyl peroxybenzoate, tert-butyl peracetate, tert-amyl peroxy (2-ethylhexyl) carbonate, di(4-methylbenzoyl) peroxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide ethane, cyclohexanone peroxide, and tert-butyl peroxy-3,5,5-trimethylhexanoate; Preferably, the auxiliary cross-linking agent includes any one of pentaerythritol triacrylate, triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate, tri(1,2-propylene glycol) diacrylate, tri(2-hydroxyethyl)isocyanuric acid triacrylate, and propoxylated trimethylolpropane triacrylate, or a combination of at least two thereof.
7. The antimony-free flame-retardant cable material according to any one of claims 1 to 6, characterized in that: The preparation raw materials also include any one or a combination of at least two of a compatibilizer, a lubricant, a silane coupling agent, a stabilizer, an ultraviolet absorber, and an antioxidant; Preferably, the preparation raw material further comprises 1-10 parts by mass of a compatibilizer; Preferably, the compatibilizer includes any one of maleic anhydride grafted polyethylene, maleic anhydride grafted polypropylene, and maleic anhydride grafted ethylene-vinyl acetate copolymer, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts by mass of a lubricant; Preferably, the lubricant comprises any one of silicone masterbatch, silicone phenol, polyethylene wax, or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts of a stabilizer by weight; Preferably, the stabilizer includes any one of zinc stearate, calcium stearate, and pentaerythritol tetrakis(β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) or a combination of at least two thereof; Preferably, the raw material for preparation further comprises 0.1-5 parts by mass of a silane coupling agent; Preferably, the silane coupling agent includes any one of an alkenyl-containing silane coupling agent, an epoxy silane coupling agent, an amino silane coupling agent, and a mercapto silane coupling agent, or a combination of at least two thereof.
8. A method for preparing the antimony-free flame-retardant cable material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: The prepared raw materials are mixed and extruded to obtain granules; The particles are made into wires through a wire extruder, and the wires are irradiated and cross-linked through an electron accelerator to obtain the antimony-free flame-retardant cable material.
9. The preparation method according to claim 8, characterized in that: The mixing is carried out in an internal mixer; Preferably, the mixing temperature is 150-180°C and the mixing time is 5-30min; Preferably, the extrusion granulation is carried out in a screw extruder; Preferably, the operating temperature of the screw extruder is 100-150°C; Preferably, the working temperature of the wire extruder is 120-190°C; Preferably, the radiation cross-linking dosage is 2-12 Mrad.
10. Use of the antimony-free flame-retardant cable material according to any one of claims 1 to 7 in building cables, wind power generation devices, solar power generation devices or electronic and electrical wires.
Citation Information
Patent Citations
Flame-retardant and antistatic polyethylene material for cable pipe and preparing method thereof
CN106117754A